Stabilization of Expansive Soil Mixture Using Human Hair Fibre (Biopolymer) - Idoui, Imane; Bekkouche, Souhila Rehab; Benzaid, Riad; Berdi, Inas (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Expansive soils sensitivity to volumetric change is one of the well-known challenges in the field of geotechnical engineering. Various attempts have been made by researchers to solve this problem. Current research presents the effect of human hair fibers on the behavior of expensive soils. A reconstituted soil of 80% kaolin as raw material and 20% bentonite with different percentages of human hair (0%, 0.5%, 1%, 1.5% and 2%) was used. The microstructure of the formulations was characterized by studying the interactions between soil and human hair using scanning electron microscopy (SEM).
Keywords: expansive soil; stabilization; human hair; SEM; compressibility